Single‐Ion Magnetostriction in Gd2O3–CeO2 Solid Solutions. (5th February 2022) - Zhang, Xiao‐Dong; Varenik, Maxim; Zvezdin, Konstantin; Ehre, David; Wachtel, Ellen; Zhu, Zengwei; Leitus, Gregory; Popov, Alexander; Zvezdin, Anatoly; Peng, Tao; Lubomirsky, Igor; Guo, Xin
Abstract: Ceria (CeO2 ) and its solid solutions with Gd2 O3 are technologically important and environmentally friendly materials with numerous interesting properties and important applications. Nevertheless, the magnetic properties of ceria are even today not fully understood, and magnetoelastic coupling in pure or doped ceria remains essentially unexplored. This has been so, in part, due to the difficulty of measuring very small magnetostrictive strains in weakly paramagnetic materials. During the last decade, however, technical advances have enabled sensitive and accurate measurements of sample deformation in high magnetic fields. Here, forced magnetostriction (MS) in Gd2 O3 ‐CeO2 solid solution ceramics (Ce1− x Gd x O2− x /2, 0 ≤ x ≤ 1) at room temperature is characterized. In a pulsed magnetic field μ0 H ≤ 60 Tesla, longitudinal MS strain is observed to depend on the square of the field amplitude and to increase linearly with Gd 3+ concentration but is not sensitive to the lattice symmetry of the ceramics. The theory attributes the origin of the observed strain to the single‐ion MS response of Gd 3+ to the crystal field via mixing of ground and excited electronic states and covalent hybridization with oxygen ligands. Contributions of charge‐compensating oxygen vacancies and/or Van Vleck paramagnetism to the observed magnetoelastic coupling are determined to be negligible. Abstract : Single‐ion magnetostriction independent of lattice symmetry is discovered in Gd2 O3 –CeO2 solid solutions under ambient conditions. With implications for novel ceramic‐based magnetic actuators, such intriguing effect is attributed to the magnetoelastic response of individual Gd 3+ ions to the crystal field via mixing of ground and excited electronic states and covalent hybridization with oxygen ligands.